"This Monstrous Scheme": Die Idee eines nationalen Wollregisters im Großbritannien des 18. Jahrhunderts und die Grenzen des Merkantilismus - Hannes Ziegler (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte (VSWG), 2024)
– The project of a national register of wool was the fever dream of mercantilism in Great Britain during the eighteenth century. For more than half a century, major parts of the English woolen traders and clothiers thereby attempted to lend administrative teeth to the ban on the exportation of English raw wool that had existed since 1660. But despite several concerted attempts, the idea never quite became reality. Why not? The article discusses the reasons for the failure of the project along with the legislative and administrative practice of raw wool regulation in eighteenth century Britain. In doing so, it also shows that the nature of this failure holds important lessons about the limits of mercantilism, economic regulation, and fiscal bureaucracy in the eighteenth century.
Keywords: N43; N63; N73; 330; fiscal bureaucracy; fiscal-military state; Great Britain; Customs and Excise; mercantilism; wool; textiles